Analisis Manajemen Logistik Dan Distribusi Pada Peternakan Unggas Di Daerah Pedesaan - Jufrijal, Jufrijal (Jurnal Ilmu Peternakan Indonesia, 2024)
Climate change has posed significant challenges to the livestock sector, affecting the production and welfare of farmers. This study aims to analyze the adaptation strategies applied by farmers in the face of climate change in the study area. Through a survey of 150 farmers, data were collected on adaptation practices, perceptions of climate change, and factors influencing adaptation decisions. The results showed that the majority of farmers have implemented diverse adaptation strategies, including increased fodder diversity, business diversification, and the use of modern agricultural technology. Although many farmers have successfully implemented these strategies, constraints such as limited access to extension services and financial resources are major challenges. The study also highlighted the importance of support from the government and relevant agencies to improve farmers' capacity to cope with climate change. The findings are expected to provide valuable insights for the development of policies that support the resilience of the livestock sector to the impacts of climate change in the future.